(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In this work we consider the regularities of changes of climate and assessed the potential impact of these changes on some of the characteristics of the hydrological regime and biota water bodies of the North of the European territory of Russia from temperate latitudes to the Arctic. Within the annual course, variation of monthly air temperature values is irregular for different seasons, with most intensive warming in January and March. In summer, variations in air temperature are multidirectional. Variations in the thermal regime led, in its turn, to later ice cover formation and earlier ice-breakup resulted in the longer ice-free period. Data analysis revealed variations in the course of precipitation of warm and cold periods. Under distinguished increase of precipitation sums, a total number of days with precipitation was revealed to be equal to or lower than its climatic norm. The total precipitation amount increase occurred due to increasing frequency of rainfalls of 10 mm and more. In winter, the snow cover height exceeded the climatic norm. As the increase of annual sums of precipitation is compensated by a rise of evapotranspiration, any trend in the total river inflow into Lake Onego is absent.